Self-curing type self-heat-conducting anti-cracking flow state solidified soil and preparation method thereof

By introducing improved measures of self-conductive and water retention capacity in the fluidized solidified soil, the problems of low strength and prone to cracking caused by hydration heat are solved, and the utilization rate of solid waste resources is improved, achieving low cost and environmentally friendly results.

CN119797872AInactive Publication Date: 2025-04-11EVERBRIGHT GREEN ENVIRONMENTAL PROTECTION TECH SERVICE (JIANGSU) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411876923.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the pouring thickness is large, the existing fluid solidified soil causes large temperature difference and severe water loss due to the heat of hydration, resulting in low strength and easy cracking. At the same time, the utilization rate of industrial solid waste resources is low, the treatment energy consumption is high, and the carbon emission is large.

Method used

Self-curing self-conducting and cracking-resistant fluid solidified soil is adopted. The raw materials include soil, slag, steel slag, desulfurization gypsum, porous ceramic granules, fluid thermal conductivity, concave and convex rod soil, water, water reducer and defoaming agent. Through specific proportioning and mixing processes, the thermal conductivity and water retention capacity of the fluid solidified soil are increased, and the risk of cracking is reduced.

Benefits of technology

It effectively improves the strength of fluid solidified soil, reduces cracking risks, improves the recycling rate of solid waste resources, reduces production costs and environmental impacts, and is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197139700000051
    Figure BDA0005197139700000051
  • Figure BDA0005197139700000061
    Figure BDA0005197139700000061
Patent Text Reader

Abstract

The invention relates to self-curing type self-heat-conducting anti-crack flow-state solidified soil and a preparation method thereof. The self-curing type self-heat-conducting anti-crack flow-state solidified soil is prepared from the following raw materials: soil, mineral slag, steel slag, desulfurized gypsum, porous ceramsite, flow-state heat-conducting silica gel, attapulgite, water, a water reducing agent and a de-foaming agent. The preparation method comprises the following steps: (1) uniformly mixing the slag, the steel slag, the desulfurized gypsum, the attapulgite and the porous ceramsite; (2) uniformly mixing the soil, the flow-state heat-conducting silica gel, the water, the water reducing agent and the defoaming agent; and (3) adding the mixture obtained in the step (1) into the mixture obtained in the step (2), and uniformly stirring until the fluidity reaches 180-220 mm. The strength of the fluid solidified soil can be effectively improved, the problem of cracking caused by large pouring thickness and slow heat dissipation of the fluid solidified soil is effectively solved, the raw materials are wide in source, the manufacturing process is simple, no complex process exists, the solid waste resource recycling rate is increased, and the method has the advantages of being low in cost, environmentally friendly and the like and is suitable for large-scale application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of civil engineering building material preparation, and in particular to a self-maintaining, self-heat-conducting, anti-cracking fluidized solidified soil and a preparation method thereof. Background Art

[0002] As a new type of green engineering material, fluidized solidified soil can be used to replace traditional backfill materials in filling projects. It has the characteristics of wide source of raw materials, self-leveling, self-compacting, and moderate strength. It can effectively solve the problems of traditional backfill materials, such as large demand for natural resources and insufficient compaction in small spaces. However, fluidized solidified soil is usually poured with a large thickness, and the curing agent in the fluidized solidified soil releases a large amount of heat during the hydration process, which makes the temperature of the fluidized solidified soil itself have a large difference with the external temperature, and a large amount of water is lost, resulting in serious water loss of the fluidized solidified soil, which in turn leads to problems such as low strength and easy cracking of the fluidized solidified soil.

[0003] In addition, the annual output of industrial solid waste is large and its resource utilization rate is low. The large amount of accumulation has caused waste of land resources and hidden dangers to ecological environment safety. Industrial solid waste has the characteristics of wide sources, many types, complex components and properties. Turning industrial solid waste into recyclable renewable resources has become an urgent problem to be solved.

[0004] In summary, it is urgent to develop a self-maintaining, self-heat-conducting, crack-resistant fluidized soil using solid waste materials. Summary of the invention

[0005] Technical problems to be solved: In view of the problems of low strength and easy cracking in existing traditional fluidized solidified soil, the inability to effectively utilize resources such as solid waste, high energy consumption and high carbon emissions in solid waste treatment, the present invention proposes a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil and a preparation method thereof, which can effectively improve the strength of the fluidized solidified soil, and effectively solve the cracking problem caused by the large pouring thickness and slow heat dissipation of the fluidized solidified soil. The raw materials are widely available, the production process is simple and there is no complicated process, which improves the recycling rate of solid waste resources, has the characteristics of low cost and environmental friendliness, and is suitable for large-scale promotion and application.

[0006] Technical solution: The first purpose of the present invention is to provide a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil, the raw materials of which are proportioned as follows by mass: 50-80 parts of soil, 10-30 parts of slag, 5-10 parts of steel slag, 5-10 parts of desulfurized gypsum, 1-5 parts of porous ceramsite, 2-9 parts of fluidized thermal conductive silica gel, 1-5 parts of attapulgite, 40-125 parts of water, 1-4 parts of water reducer, and 1-4 parts of defoaming agent.

[0007] Preferably, the soil is waste soil or waste mud in construction projects. The relevant heavy metals and pollution limits meet the relevant provisions of standard GB15618-1995. If the soil is waste mud, it is sieved after air drying and its moisture content is measured to control the total moisture content of the self-curing self-heat-conducting anti-cracking fluidized solidified soil.

[0008] Preferably, the slag is S95 grade granulated blast furnace slag.

[0009] Preferably, the basicity of the steel slag is between 3.0 and 4.5.

[0010] Preferably, the calcium sulfate content in the desulfurized gypsum is greater than or equal to 83%.

[0011] Preferably, the porous ceramsite is high-strength shale porous ceramsite with a particle size of less than 1.18 mm and a water absorption rate of 12%.

[0012] Preferably, the fluid thermally conductive silicone is epoxy resin thermally conductive silicone or silicone rubber thermally conductive silicone.

[0013] Preferably, the attapulgite has a particle size of 400 mesh and a water absorption rate of 24%.

[0014] Preferably, the water reducer is a high-performance polycarboxylic acid water reducer with a water reduction rate of ≥30%; the defoamer is emulsified silicone oil, a high-carbon alcohol fatty acid ester complex or polyoxyethylene polyoxypropylene pentaerythritol ether.

[0015] The second object of the present invention is to provide a method for preparing the self-curing, self-heat-conducting, anti-cracking fluidized solidified soil, the steps of which are as follows:

[0016] Step 1: Evenly mix slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite to obtain a mixture A;

[0017] Step 2: Evenly mix the soil, fluidized thermal conductive silica gel, water, water reducing agent and defoaming agent to obtain a mixture B;

[0018] Step 3: Add mixture A into mixture B and stir evenly to make the fluidity reach 180-220 mm, and then self-curing, self-heat-conducting, anti-cracking fluidized solidified soil can be obtained.

[0019] Beneficial effects:

[0020] (1) The addition of the fluidized heat-conductive silica gel in the present invention allows the fluidized solidified soil to be heat-conducted when a large amount of hydration heat is generated during the solidification process, thereby reducing the temperature difference between the inside and outside of the fluidized solidified soil and reducing the risk of cracking of the fluidized solidified soil.

[0021] (2) The present invention mixes fluidized thermally conductive silica gel, porous ceramsite and attapulgite in a certain proportion, so that during the curing process of the fluidized solidified soil, the thermally conductive silica gel can extract the heat generated by the hydration reaction inside the fluidized solidified soil without affecting the porous ceramsite and attapulgite's absorption and preservation of moisture in the fluidized solidified soil. When the internal humidity of the fluidized solidified soil is low, the porous ceramsite and attapulgite further release the moisture stored therein to meet the moisture demand of the fluidized solidified soil, thereby reducing the risk of cracking of the fluidized solidified soil in the later stage.

[0022] (3) The raw materials of the present invention are widely available, the production process is simple and without complicated processes, and solid waste materials are applied on a large scale, thereby improving the recycling rate of solid waste resources and solving problems such as high energy consumption and high carbon emissions. While ensuring the effect, it has the characteristics of low cost and environmental friendliness, and is suitable for large-scale promotion and application. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0024] Unless otherwise specified, the raw materials used in the examples of this specification are all from common commercially available products.

[0025] The soil is waste soil from construction projects, and its related heavy metals and pollution limits comply with the relevant provisions of standard GB15618-1995;

[0026] The slag was S95 grade granulated blast furnace slag purchased from Henan Huifeng Materials Co., Ltd., with a particle size of 500 mesh;

[0027] The basicity of steel slag is between 3.0 and 4.5, purchased from Dingnuo Quartz Sand Factory, with a particle size of 300 to 500 mesh;

[0028] The calcium sulfate content in the desulfurized gypsum is more than 83%, purchased from Fujian Building Materials Co., Ltd., and the particle size is 300-500 mesh;

[0029] The porous ceramsite is a high-strength shale porous ceramsite purchased from Anhui Mozi Environmental Protection Technology Co., Ltd., with a particle size of less than 1.18 mm and a water absorption rate of 12%;

[0030] Fluid thermally conductive silicone is organic silicone rubber thermally conductive silicone, purchased from Zihao Adhesive Products Co., Ltd.;

[0031] Attapulgite was purchased from Xinlei Mineral Powder Processing Co., Ltd. with a particle size of 400 mesh and a water absorption rate of 24%;

[0032] The water reducer is a high performance polycarboxylate water reducer, model Water reduction rate ≥ 30%, purchased from Jiangsu Subote New Materials Co., Ltd.;

[0033] Defoaming agent is Concrete defoamer was purchased from Jiangsu Subote New Materials Co., Ltd.

[0034] Example 1

[0035] The present embodiment provides a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil, which comprises, by mass, 50 parts of soil, 15 parts of slag, 5 parts of steel slag, 5 parts of desulfurized gypsum, 1 part of porous expanded clay, 2 parts of fluidized thermal conductive silica gel, 1 part of attapulgite, 1 part of water reducer, 1 part of defoamer, and 47 parts of water.

[0036] The method for preparing the self-curing, self-heat-conducting, anti-cracking fluidized solidified soil comprises the following steps:

[0037] S1. Mix the weighed slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite;

[0038] S2. Mix the weighed soil, fluidized thermal conductive silica gel, water, water reducing agent and defoaming agent evenly;

[0039] S3. Add the mixture of step S1 to the mixture of step S2 and stir evenly until the fluidity reaches 180-220 mm.

[0040] Example 2

[0041] The present embodiment provides a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil, which comprises, by mass, 60 parts of soil, 20 parts of slag, 8 parts of steel slag, 8 parts of desulfurized gypsum, 2 parts of porous expanded clay, 4 parts of fluidized thermal conductive silica gel, 2 parts of attapulgite, 1 part of water reducer, 1 part of defoaming agent, and 70 parts of water.

[0042] The method for preparing the self-curing, self-heat-conducting, anti-cracking fluidized solidified soil comprises the following steps:

[0043] S1. Mix the weighed slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite;

[0044] S2. Mix the weighed soil, fluidized thermal conductive silica gel, water reducing agent and defoaming agent evenly;

[0045] S3. Add the mixture of step S1 to the mixture of step S2 and stir evenly until the fluidity reaches 180-220 mm.

[0046] Example 3

[0047] The present embodiment provides a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil, which comprises, by mass, 70 parts of soil, 25 parts of slag, 10 parts of steel slag, 10 parts of desulfurized gypsum, 4 parts of porous expanded clay, 6 parts of fluidized thermal conductive silica gel, 4 parts of attapulgite, 1 part of water reducer, 1 part of defoaming agent, and 95 parts of water.

[0048] The method for preparing the self-curing, self-heat-conducting, anti-cracking fluidized solidified soil comprises the following steps:

[0049] S1. Mix the weighed slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite;

[0050] S2. Mix the weighed soil, fluidized thermal conductive silica gel, water reducing agent and defoaming agent evenly;

[0051] S3. Add the mixture of step S1 to the mixture of step S2 and stir evenly to make the fluidity reach 180-220mm.

[0052] Example 4

[0053] The present embodiment provides a self-maintaining, self-heat-conducting, crack-resistant fluidized solidified soil, which comprises, by mass, 80 parts of soil, 30 parts of slag, 10 parts of steel slag, 10 parts of desulfurized gypsum, 5 parts of porous expanded clay, 9 parts of fluidized thermal conductive silica gel, 5 parts of attapulgite, 4 parts of water reducer, 4 parts of defoamer, and 125 parts of water.

[0054] The method for preparing the self-curing, self-heat-conducting, anti-cracking fluidized solidified soil comprises the following steps:

[0055] S1. Mix the weighed slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite;

[0056] S2. Mix the weighed soil, fluidized thermal conductive silica gel, water reducing agent and defoaming agent evenly;

[0057] S3. Add the mixture of step S1 to the mixture of step S2 and stir evenly to make the fluidity reach 180-220mm.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that porous ceramsite, fluid thermal conductive silica gel and attapulgite are not added.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 2 is that porous ceramsite, fluid thermal conductive silica gel and attapulgite are not added.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 3 is that porous ceramsite, fluid thermal conductive silica gel and attapulgite are not added.

[0064] Comparative Example 4

[0065] The difference between this comparative example and Example 1 is that porous ceramsite and fluid thermally conductive silica gel are not added.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that fluidized thermally conductive silica gel and attapulgite are not added.

[0068] Comparative Example 6

[0069] The difference between this comparative example and Example 1 is that porous ceramsite and attapulgite are not added.

[0070] After the preparation is completed according to the above preparation method, the self-curing self-heat-conducting anti-cracking fluidized solidified soil mixtures prepared in Examples 1 to 3 and Comparative Examples 1 to 6 need to be tested for fluidity, unconfined compressive strength and anti-cracking performance, as follows:

[0071] 1) Liquidity test

[0072] The fluidity test is carried out according to ASTM D4843-1988. The main equipment includes a 50cm×50cm glass plate, a Φ80mm×80 cylinder, a ruler, etc. The ruler measures the maximum diameter and the minimum diameter of the mixture after it is spread out, and the average of the two is the flow value.

[0073] 2) Unconfined compressive strength test

[0074] The unconfined compressive strength test was carried out according to GB / T50123-2019. The specimen size is Φ39.1mm×80mm and it was cured in a curing box at a temperature of 20±2℃ and a humidity greater than 95% to the specified age.

[0075] 3) Crack resistance test

[0076] Referring to the provisions of the Technical Code for Prevention and Control of Cracks in Construction Engineering (JKGJ / T317-2014), cracks are evaluated according to the following three parameters of the crack area method, and concrete is graded according to the following provisions based on the crack parameters.

[0077] (1) The average crack area a is less than 10 mm 2 ; (2) The number of cracks per unit area b is less than 10 / m 2 ; (3) The crack area ratio c is less than 100 mm 2 / m 2 ;

[0078] According to the evaluation limit, the anti-cracking performance of fluidized solidified soil is divided into the following five levels;

[0079] Level I: the specimen has no cracks or only slight cracks;

[0080] Level II: all test data do not exceed the evaluation limit;

[0081] Level III: one of the three test data exceeds the evaluation limit;

[0082] Level IV: two of the three test data exceed the evaluation limit;

[0083] Level V: All three test data exceed the evaluation limits.

[0084] For grades IV and V, it can be evaluated that their crack resistance is poor.

[0085] The test results of the relevant properties of the self-curing, self-heat-conducting, crack-resistant fluidized soil are shown in Tables 1 and 2.

[0086] Table 1 Fluidity and unconfined compressive strength of self-curing self-heat-conducting anti-cracking fluidized solidified soil prepared in Examples and Comparative Examples

[0087]

[0088] Table 2 Anti-cracking performance of self-curing self-heat-conducting anti-cracking fluidized solidified soil prepared in Examples and Comparative Examples

[0089]

[0090] It can be seen from Table 1 and Table 2 that the fluidity of the self-curing, self-heat-conducting, anti-crack fluidized solidified soil of the present invention is not much different from that in the comparative example, and is basically at the same level, but the non-lateral compressive strength and crack resistance of the self-curing, self-heat-conducting, anti-crack fluidized solidified soil of the present invention are higher than those of the comparative example without porous ceramsite, fluidized heat-conducting silica gel and attapulgite or only one of them. The self-curing, self-heat-conducting, anti-crack fluidized solidified soil of the present invention has a wide range of raw materials, a simple production process, no complicated process, and improves the recycling rate of solid waste resources. It has the characteristics of low cost and environmental friendliness while ensuring the application effect, and has broad application prospects.

[0091] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A self-curing, self-heat-conducting, anti-cracking fluidized solidified soil, characterized in that: The raw materials are proportioned as follows by mass: 50-80 parts of soil, 10-30 parts of slag, 5-10 parts of steel slag, 5-10 parts of desulfurized gypsum, 1-5 parts of porous ceramsite, 2-9 parts of fluidized thermal conductive silica gel, 1-5 parts of attapulgite, 40-125 parts of water, 1-4 parts of water reducer, and 1-4 parts of defoamer.

2. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The soil is waste soil or waste mud in construction projects.

3. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The slag is S95 grade granulated blast furnace slag.

4. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The basicity of the steel slag is between 3.0 and 4.

5.

5. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The calcium sulfate content in the desulfurized gypsum is greater than or equal to 83%.

6. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The porous ceramsite is high-strength shale porous ceramsite with a particle size of less than 1.18 mm and a water absorption rate of 12%.

7. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The fluid thermally conductive silicone is epoxy resin thermally conductive silicone or organic silicone rubber thermally conductive silicone.

8. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The attapulgite particle size is 400 meshes and the water absorption rate is 24%.

9. The self-curing, self-heat-conducting, anti-cracking fluidized solidified soil according to claim 1, characterized in that: The water reducer is a high-performance polycarboxylic acid water reducer with a water reduction rate of ≥30%; the defoamer is emulsified silicone oil, a high-carbon alcohol fatty acid ester complex or polyoxyethylene polyoxypropylene pentaerythritol ether.

10. The method for preparing the self-curing, self-heat-conducting, crack-resistant fluidized solidified soil according to any one of claims 1 to 9, characterized in that: Here are the steps: Step 1: Evenly mix slag, steel slag, desulfurized gypsum, attapulgite and porous ceramsite to obtain a mixture A; Step 2: Evenly mix the soil, fluidized thermal conductive silica gel, water, water reducing agent and defoaming agent to obtain a mixture B; Step 3: Add mixture A into mixture B and stir evenly to make the fluidity reach 180-220 mm, and then self-curing, self-heat-conducting, anti-cracking fluidized solidified soil can be obtained.

Citation Information

Patent Citations

  • Premixed flow-state stabilized soil

    CN107401159A

  • Water-retention heat-release anti-crack concrete and preparation method thereof

    CN113735507A

  • Self-curing type organic-inorganic composite regenerated flow-state solidified soil and preparation method thereof

    CN117024096A